Bronchial aneurysm secondary to tuberculosis presenting with fatal hemoptysis: a case report and review of the literature - Cheng, Yu-Sheng; Lu, Zhi-Wei (Journal of Thoracic Disease, 2014)
Fatal hemoptysis is a serious complication of pulmonary tuberculosis, which can rarely be due to a bronchial aneurysm. Here, we present a case of fatal hemoptysis due to bronchial aneurysm occurred in a 59-year-old patient of Han ethnicity suffering from active pulmonary tuberculosis. Meanwhile, we perform a literature review of reported cases to stress detailed radiological examination is needed prior to bronchoscopy to exclude the possibility of aneurysm existent in proximity to the lesions caused by mycobacterium tuberculosis. Urgent and effective treatment is needed to control such life-threatening bleeding, such as rigid bronchoscopy, endovascular therapy and surgery, and endovascular stent-graft repair.